Features of a Gaussian beam near-field diffraction upon variations in the relief height of subwavelength silicon optical elements - D.A. Savelyev (Компьютерная оптика)
Features of the near-field diffraction of Gaussian beams and Laguerre-Gauss modes by silicon subwavelength optical elements with varying relief height were studied in this paper using a finite-difference time-domain method. Diffractive axicons and subwavelength ring gratings were considered as the optical elements with varying relief height. It was shown that the height of individual rings of the ring grating relief can be selected in such a way that the focal spot size is reduced to 0.26λ, an extended intensity line of length up to 4.88λ is generated and optical traps are formed.